2018
DOI: 10.1016/j.jacc.2018.09.076
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Change in Galectin-3 and Incident Cardiovascular Outcomes

Abstract: Background Galectin-3 (Gal-3) has been associated with heart failure (HF) and poor cardiovascular outcomes. However, the effect of longitudinal changes in Gal-3 on clinical outcomes remains unclear. Objectives We sought to study clinical determinants of change in Gal-3 among communitydwelling individuals. Further, we sought to examine the role of serial Gal-3 measurements in predicting risk of future HF, cardiovascular disease (CVD) and mortality. Methods A total of 2,477 participants of the Framingham Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 32 publications
0
37
0
1
Order By: Relevance
“…Recently, Gal-3 has been indicated to be involved in the following broad pathological processes: Inflammation [9], fibrosis, cell-to-cell [10,11] or cell-to-matrix [12] contacts, cell proliferation [13,14], and protection from apoptosis [15,16]. Furthermore, many studies have revealed that Gal-3 expression is detected in many disease conditions, such as heart disease [17][18][19][20][21][22][23], kidney disease [24][25][26][27], diabetes mellitus [24,25,28], viral infection [29][30][31][32], autoimmune disease [33][34][35][36], neurodegenerative disorders [37][38][39][40][41][42], and tumor formation [43][44][45][46][47][48][49][50][51][52].…”
Section: Clinical Significance and Applications Of Galectine-3 (Gal-3)mentioning
confidence: 99%
“…Recently, Gal-3 has been indicated to be involved in the following broad pathological processes: Inflammation [9], fibrosis, cell-to-cell [10,11] or cell-to-matrix [12] contacts, cell proliferation [13,14], and protection from apoptosis [15,16]. Furthermore, many studies have revealed that Gal-3 expression is detected in many disease conditions, such as heart disease [17][18][19][20][21][22][23], kidney disease [24][25][26][27], diabetes mellitus [24,25,28], viral infection [29][30][31][32], autoimmune disease [33][34][35][36], neurodegenerative disorders [37][38][39][40][41][42], and tumor formation [43][44][45][46][47][48][49][50][51][52].…”
Section: Clinical Significance and Applications Of Galectine-3 (Gal-3)mentioning
confidence: 99%
“…Indeed, longitudinal changes in galectin-3 levels predicted incident HF in both the FHS (n = 2477) and PRE-VEND (n = 5958) cohorts, also after extensive adjustment for cardiovascular risk factors. 90,91 To date, no study has examined whether longitudinal changes in galectin-3 predict new-onset HF differentially in men and women.…”
Section: Heart Failure Prediction and Prognosismentioning
confidence: 99%
“…Galectin‐3 (Gal‐3) is a β‐galactoside‐specific lectin that binds to intracellular and extracellular glycoproteins regulating their function particularly under diseased conditions (Meijers, Lopez‐Andres, & de Boer, ; Nguyen et al, ; Takemoto et al, ). Clinically, Gal‐3 is regarded as a biomarker predicting the risk of heart failure, atrial fibrillation, or all‐cause mortality (Filipe, Meijers, Rogier van der Velde, & de Boer, ; Ghorbani et al, ). Meanwhile, Gal‐3 is implicated as a causative mediator of cardiac inflammation and fibrosis (Nguyen et al, ; Rabinovich & Toscano, ; Suthahar et al, ; Takemoto et al, ; L. Yu et al, ).…”
Section: Introductionmentioning
confidence: 99%